CircBIRC6 affects prostate cancer progression by regulating miR-574-5p and DNAJB1 - Zhao, Bin; Yang, Jinye; Ran, Fengming; Shi, Yuanlong; Yang, Libo; Duan, Yuanpeng; Shi, Zhiyu; Li, Xin; Zhang, Jianpeng; Li, Zhiyao; Wang, Jiansong (Cancer biology & therapy, 2024)
Prostate cancer (PCa) is among the three main types of cancer. Although prostate-specific antigen (PSA) is routinely tested, it has disadvantages, such as poor prognostic ability. Therefore, finding more PCa markers and therapeutic targets remains a subject of study. CircRNAs have been found to have regulatory roles in various diseases, such as diabetes, Central Nervous System (CNS) neuropathy, etc. where their application in cancer is even more valuable. Therefore, this paper aims to search for differentially expressed circRNAs in PCa and find downstream targeting pathways related to autophagy. By detecting the expression of circRNA in the samples, hsa_circ_0119816 was finally identified as the research target. The properties of circRNA were verified by RNase R, actinomycin D, and fluorescence in situ hybridization (FISH). The downstream target miRNAs and target proteins were predicted by an online database, and the targeting relationship was verified using dual luciferase and RNA Immunoprecipitation. The effects of circRNAs and their downstream signalling pathways on prostate cancer cell proliferation, migration, EMT and autophagy were examined by CCK-8, Transwell, immunofluorescence and Western blotting. CircBIRC6 is highly expressed in prostate cancer samples. Knockdown of its expression inhibits cell proliferation, invasion, EMT and autophagy and promotes apoptosis. CircBIRC6/miRNA-574-5p/DNAJB1 is a molecular axis that regulates prostate cancer cells.